Kritik des Anthropozäns: Plädoyer für eine neue Humanökologie - Hobuß, Steffi; Manemann, Jürgen (transcript, 2014)
»Welcome to the Anthropocene« - a 2011 title of »The Economist« initiating a new climate policy debate about mankind and the new »Age of Humans«. Today, the term is not only found in the gazettes, but also in science, politics, and culture. But what lies behind the term and where does it come from? Jürgen Manemann introduces to the debate, points out the dangers of the theory of the anthropocene, and calls for a human ecology that aims at a transformation of civil society towards a »cultural society« (Adrienne Goehler). It is not time for a new humanization of the world, but a deeper humanization of mankind. Review»This book offers information about historical and current debates around the relation of the human with nature, contains approaches for the ongoing critique of the anthropocene and encourages further thought and investigation.« Herbert Hörz, Leibniz Online, 17 (2015)